2014
DOI: 10.1111/hdi.12154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation on anti‐oxidative effects of vitamin E‐coated membrane dialyzer in patients on chronic hemodialysis

Abstract: Hemodialysis (HD) with the use of vitamin E-coated membrane (VEM) dialyzers is shown to exert anti-inflammatory and antioxidative effects in patients with end-stage renal disease on HD. However, the association of baseline inflammatory status with the antioxidative effects of VEM has not been investigated thus far. Thirty-five stable end-stage renal disease patients treated with VEM for 6 months were enrolled in the present prospective, observational cohort study. For the previous 3 months minimum, 17 (48%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(88 reference statements)
1
1
0
Order By: Relevance
“…Many studies have shown the antioxidant effects of a vitamin E-coated dialyzer in vivo [1,2]. In our vitro study, a vitamin E-coated dialyzer decreased intracellular ROS production and MDA levels; therefore, we confirmed the effects of the vitamin E-coated dialyzer in vitro.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Many studies have shown the antioxidant effects of a vitamin E-coated dialyzer in vivo [1,2]. In our vitro study, a vitamin E-coated dialyzer decreased intracellular ROS production and MDA levels; therefore, we confirmed the effects of the vitamin E-coated dialyzer in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have shown anti-oxidative effects of a vitamin E-coated dialyzer in vivo [1,2]. Nonetheless, in vitro studies are rare [3], and almost all such studies have involved mini-module dialysis membranes [4].…”
Section: Introductionmentioning
confidence: 99%